PENGARUH TOTAL QUALITY MANAGEMENT, KUALITAS PELAYANAN, DAN HARGA PRODUK TERHADAP KEPUASAN PELANGGAN PROGRAM GURU MERDEKA BELAJAR DI PLATFORM SEKOLAH.MU - Sarah Paskalia Afridianayu Fiestasari (Jurnal Ekonomi Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of Total Quality Management, customer’s satisfaction, and the product prices on customer’s satisfaction for the Guru Merdeka Belajar program on Sekolah.mu platform. The method used is a quantitative method with statistical analysis technique using Multiple Linier Regression, correlation, determination, and hypothesis testing, the result show that Total Quality Management has a positive effect on customer’s satisfaction, product prices have a positive effect on customer’s satisfaction.